In Memoriam Prof. Vello Volt (18.10.1928–26.10.2014). Mit Zusammenfassung - Lõokene, Inga (Estonian Discussions on Economic Policy, 2015)
Vello Volt was born in Tartu on 18 October 1928. The fate provided him the opportunity to develop his talents and abilities for 86 years and share his knowledge with students. He acquired his basic knowledge in the primary schools and secondary schools of Tartu and Tallinn in 1936–1948. In 1948–1952 he studied the speciality of finance in the Faculty of Economics of the Tallinn Polytechnical Institute (the current Tallinn University of Technology, TUT) and graduated with the diploma cum laude. In 1959, V. Volt started post-graduate studies (current doctoral studies) at the Tallinn Polytechnical University. He defended the thesis of a Candidate of Economics (PhD) on 18 June 1964 in Tartu. He has been characterised as a searcher for new methodological approaches to economic challenges and as a researcher who skilfully combined industrial economics with statistics. In 1984, V.Volt published the textbook Tööstusettevõtte majandusanalüüs (Business Analysis of Industrial Enterprises). Until publishing of that textbook, these subjects had been taught in institutions of higher education only on the basis of a few brochures published in Estonian. Different treatments of the same subjects by different authors, also outdated materials had been confusing for students. Thus it had been difficult to obtain a comprehensive overview of business analysis. V.Volt, however, reviewed all necessary theoretical and practical issues of business analysis; presented a more in depth treatment of factor analysis; the economic effect of technical innovations and work procedures and the analysis of interrelations of economic factors acquired a new approach; algorithms of the main economic parameters from the aspects of business analysis were presented. The authors wrote the book according to the study programmes of subjects of economics (accounting, business analysis and credit) in institutions of higher education. The use of numerous examples was of great value. The main source of information was the annual report of an enterprise but also other sources were referred to. This made the textbook usable as a manual also for practitioners. In 1991, Vello Volt, Peeter Riit and Andres Root established Riit–Root–Volt, the first audit office in the Republic of Estonia. All three had the background of the Chair of Accounting of the Tallinn Polytechnical Institute and also a large number of chief accountants of Estonian enterprises had acquired their education in economics there. It became a basis for the new company. The current name of the audit office is KPMG Estonia and it has approximately a hundred employees in Estonia. Professor Vello Volt as an esteemed business analyst and academic loved by his students and colleagues passed away on 26 October 2014.